Q[7]@mof composite material and preparation method and application thereof

CN122999154APending Publication Date: 2026-10-30GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611107217.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,传统的单MOF材料在实际应用中普遍存在固有缺陷

Benefits of technology

[0025]本发明与现有技术相比,有益效果有:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999154A_ABST
    Figure CN122999154A_ABST
Patent Text Reader

Abstract

The application discloses a Q[7]@MOF composite material and a preparation method and application thereof. The Q[7]@MOF composite material comprises seven-membered cucurbituril and NH2-MIL-125(Ti) assembled together. The preparation method comprises the following steps: dissolving the seven-membered cucurbituril in a mixed solvent of water and acetic acid to obtain a seven-membered cucurbituril solution; adding the seven-membered cucurbituril solution into a NH2-MIL-125(Ti) dispersion liquid, stirring and reacting in the dark at 35-45 DEG C, gradually changing the color of the mixed liquid into dark yellow, stopping the reaction, washing and drying the solid to obtain the Q[7]@MOF composite material. The Q[7]@MOF composite material can be used as or for manufacturing an adsorbent, has excellent adsorption strength and adsorption effect on radioactive iodine element pollutants, and can replace an iodine adsorber in the prior art which has high use cost and large solid waste output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of iodine adsorption technology, specifically to a Q[7]@MOF composite material and its preparation method and application. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Radioactive iodine isotopes (such as...) 129 I, 131 I) These are considered highly hazardous nuclear contaminants, posing a serious and long-term threat to the ecological environment and human health. Due to their high volatility, strong mobility, and long half-life, these iodine nuclides easily diffuse into water systems and the atmosphere, and readily enter the biocycle through respiration and water ingestion. Once accumulated in the human body, radioactive iodine can cause irreversible damage to the thyroid gland and trigger a series of genetic and cytotoxic effects. Therefore, effective monitoring and thorough removal of radioactive iodine is a crucial core issue in nuclear environmental safety, nuclear accident emergency response, and radioactive wastewater remediation. However, for current environmental remediation materials, simultaneously achieving real-time, visualized monitoring and efficient, deep removal of trace amounts of radioactive iodine from complex water and air matrices remains a significant practical challenge.

[0004] Metal-organic frameworks (MOFs), as a class of crystalline porous materials with tunable pore structures, large specific surface areas, and modifiable functional groups, have become promising candidates for the remediation of radioactive contaminants. Thanks to their inherent porous framework, MOFs can provide unobstructed diffusion channels for iodine species, endowing them with preliminary iodine adsorption capabilities. However, traditional single-MOF materials generally suffer from inherent defects in practical applications. The limited density of surface active sites and the monotonous adsorption mechanism greatly restrict their adsorption saturation capacity and deep removal efficiency for iodine contaminants. Furthermore, most pristine MOFs lack response recognition characteristics for iodine species, making it impossible to achieve real-time on-site monitoring of the iodine capture process, which severely limits their practical application value in the intelligent integrated remediation of radioactive iodine contamination. Therefore, rational structural design and functional modification of MOF materials to overcome the performance bottlenecks of single-component materials are key to developing high-performance iodine remediation systems.

[0005] Molecular modification strategies have become an effective means of constructing high-efficiency composite functional materials. They can integrate the structural advantages of porous substrates and supramolecular host-guest characteristics to achieve synergistic functional optimization. Cucurbita (Q[7]) is a typical macrocyclic supramolecular compound with a unique rigid hydrophobic cavity and a negatively charged carbonyl edge portal structure. It exhibits excellent specific host-guest recognition ability for halogen molecules and iodine ions, and can provide precise supramolecular binding sites for iodine pollutants, making up for the shortcomings of single MOF materials in terms of specific adsorption capacity. More importantly, the electronegative carbonyl oxygen (C=O) at the entrance of Q[7] can form a strong ionic dipole interaction with the protonated amino group on the amino-functionalized MOF substrate. This unique electrostatic interaction can tightly anchor the Q[7] molecule to the MOF framework, effectively improving the structural stability of the composite material and avoiding structural collapse and loss of active sites caused by simple physical composites. Summary of the Invention

[0006] This invention provides a Q[7]@MOF composite material, its preparation method, and its application. This composite material has excellent adsorption strength and adsorption effect on radioactive iodine pollutants, and can replace the iodine adsorbers used in the prior art, which are costly and produce a large amount of solid waste.

[0007] The specific technical solution of this invention is as follows: In a first aspect, the present invention provides a Q[7]@MOF composite material comprising a seven-membered cucurbit ring (Q[7]) and NH2-MIL-125(Ti) assembled together by supramolecular assembly.

[0008] The electronegative carbonyl oxygen (C=O) at the Q[7] port can form a strong ion-dipole interaction with the protonated amino group on the aminated MOF substrate NH2-MIL-125(Ti). This unique electrostatic interaction can tightly anchor the Q[7] molecule to the MOF framework, effectively improving the structural stability of the composite material and avoiding structural collapse and loss of active sites caused by simple physical composites.

[0009] In this work, we report a novel Q[7]-mediated supramolecular modification strategy. The strong ion-dipole interaction between the electronegative carbonyl oxygen (C=O) at the Q[7] port and the protonated amino group on the organometallic material NH2-MIL-125(Ti) anchors Q[7] onto the outer surface of NH2-MIL-125(Ti), and a novel supramolecular host-guest composite material Q[7]@NH2-MIL-125 is successfully prepared. The introduction of Q[7] endows the composite system with dual functional properties of simultaneous iodine capture and fluorescence response. The charge transfer interaction between the iodine species and the composite material triggers significant changes in fluorescence signal during iodine absorption, constructing a reliable real-time fluorescence monitoring platform for radioactive iodine pollution. This work innovatively integrates supramolecular host-guest chemistry and MOF functional materials, achieving an organic combination of real-time fluorescence monitoring and efficient enrichment of radioactive iodine. The constructed Q[7]@NH2-MIL-125 composite material overcomes the performance limitations of single MOF materials, provides a feasible technical approach and reliable material support for the remediation of radioactive iodine pollution in the environment, and broadens the functional application boundaries of cucurbituril-based supramolecular composite materials in the field of nuclear environmental protection.

[0010] Furthermore, the Q[7]@MOF composite material has an octahedral granular morphology.

[0011] In some preferred embodiments, the molar ratio of the seven-membered cucurbit ring and NH2-MIL-125(Ti) in the Q[7]@MOF composite material is (0.2~0.3):1, and more preferably (0.24~0.25):1. Under these preferred conditions, the composite material has a higher Q[7] loading rate and can exhibit better adsorption strength and adsorption effect for iodine.

[0012] In a second aspect, the present invention provides a method for preparing the Q[7]@MOF composite material described in the first aspect, comprising: A solution of seven-membered cucurbitacin was obtained by dissolving the seven-membered cucurbitacin in a mixed solvent of water and acetic acid. The seven-membered cucurbitacin solution was added dropwise to the NH2-MIL-125(Ti) dispersion. The mixture was stirred at 35~45℃ (e.g., 40℃) in the dark. The color of the mixture gradually turned dark yellow. After the reaction was completed, the solid was washed and dried to obtain the Q[7]@MOF composite material.

[0013] In some preferred embodiments, in the preparation method, the volume ratio of water to acetic acid in the mixed solvent is (1~2):(1~2).

[0014] In this invention, NH2-MIL-125(Ti) is a prior art material and can be prepared using existing techniques. This invention does not require special preparation in this regard.

[0015] In some preferred embodiments, the solvent in the NH2-MIL-125(Ti) dispersion in the preparation method includes methanol.

[0016] In some preferred embodiments, the preparation method is described in which the addition is carried out drop by drop, and is performed under stirring.

[0017] In some preferred embodiments, the stirring reaction time in the preparation method is 8-12 h.

[0018] Thirdly, the present invention provides the application of the Q[7]@MOF composite material described in the first aspect as or for use in the manufacture of adsorbents. The adsorbent can be used to adsorb iodine.

[0019] Fourthly, the present invention provides the application of the Q[7]@MOF composite material described in the first aspect for the adsorption of iodine.

[0020] Furthermore, the iodine may include iodine vapor, iodine molecules in an iodine solution, or I3. - One or more of the following (iodine 3 anions): [Iodine 3 anions]. Furthermore, the iodine solution may include an aqueous iodine solution, etc.

[0021] In some preferred embodiments, the Q[7]@MOF composite material is used to adsorb iodine at a temperature of room temperature to 130°C, such as 25°C, 70°C, etc.

[0022] For example, the temperature at which the Q[7]@MOF composite material is used to adsorb iodine vapor can be 70~130℃, etc.

[0023] For example, the Q[7]@MOF composite material is used to adsorb iodine molecules and / or I3 in iodine (water) solution. - The temperature can be 25℃, etc.

[0024] This invention uses seven-membered cucurbitacin and NH2-MIL-125(Ti) as raw materials to prepare Q[7]@NH2-MIL-125(Ti) adsorbent material. Q[7]@NH2-MIL-125(Ti) adsorbent material has an octahedral particle morphology and can be used for the adsorption and separation of elemental iodine and iodide ion pollutants. It exhibits excellent iodine adsorption capacity and rate, and also shows a faster adsorption kinetic rate than Q[7] and NH2-MIL-125(Ti) alone. It can also be recycled multiple times.

[0025] Compared with the prior art, the beneficial effects of this invention are as follows: This invention successfully prepared a novel supramolecular MOF composite material Q[7]@NH2-MIL-125 through a simple supramolecular modification strategy. The introduction of Q[7] endowed the composite system with dual functional characteristics of simultaneous iodine capture and fluorescence response. The charge transfer interaction between iodine species and the composite material triggered significant changes in fluorescence signal during iodine absorption, constructing a reliable real-time fluorescence monitoring platform for radioactive iodine pollution. System experiments and structural analysis confirmed that the excellent iodine removal performance of Q[7]@NH2-MIL-125 stemmed from a significant triple synergistic effect. Specifically, the rigid cavity of Q[7] provided specific supramolecular host-guest recognition for the selective binding of iodine species; the amino group (-NH2) on the NH2-MIL-125 backbone acted as an electron donor, forming charge transfer complexes and halogen bonds with iodine pollutants, significantly enhancing the adsorption binding affinity; at the same time, the inherent titanium oxide clusters and hierarchical porous structure of the MOF substrate provided abundant physical adsorption sites and unobstructed diffusion channels, effectively accelerating the adsorption kinetics of iodine species.

[0026] This work innovatively integrates supramolecular host-guest chemistry and MOF functional materials, achieving an organic combination of real-time fluorescence monitoring and efficient deep purification of radioactive iodine. The constructed Q[7]@NH2-MIL-125 composite material overcomes the performance limitations of single MOF materials, providing a feasible technical approach and reliable material support for the remediation of radioactive iodine pollution in the aquatic environment, and broadening the functional application boundaries of cucurbituril-based supramolecular composite materials in the field of nuclear environmental protection. Attached Figure Description

[0027] Figure 1 The image is a scanning electron microscope (SEM) image of the Q[7]@NH2-MIL-125 adsorbent of Example 1.

[0028] Figure 2 The Fourier transform infrared (FT-IR) spectra of Q[7]@NH2-MIL-125 adsorbent and Q[7] and NH2-MIL-125 in Example 1 are shown.

[0029] Figure 3 The image shows the X-ray diffraction (XRD) patterns of the Q[7]@NH2-MIL-125 adsorbent of Example 1 and Q[7] and NH2-MIL-125.

[0030] Figure 4 The N1s fine spectrum of the X-ray photoelectron spectroscopy (XPS) of the Q[7]@NH2-MIL-125 adsorbent that adsorbed iodine vapor in Example 2 is shown.

[0031] Figure 5 This is the UV-Vis spectrophotometer of the iodine aqueous solution adsorption test in Example 3.

[0032] Figure 6 The image shows the UV-Vis spectrophotometer of the adsorption test of the iodine-potassium iodide mixed solution in Example 4.

[0033] Figure 7 The graph shows the iodine adsorption results after the Q[7]@NH2-MIL-125 adsorbent was reused 5 times in Example 5.

[0034] Figure 8 The graph shows the adsorption capacity of iodine 3 negative ions after the Q[7]@NH2-MIL-125 adsorbent was reused 5 times in Example 6.

[0035] Figure 9 The color change diagram is shown in Example 7 for the iodine vapor adsorption experiment of filter cake loaded with Q[7]@NH2-MIL-125 adsorbent.

[0036] Figure 10 The color change diagram is shown in Example 8, which is an adsorption experiment of filter cake iodine 3 anion aqueous solution loaded with Q[7]@NH2-MIL-125 adsorbent.

[0037] Figure 11 The figure shows the iodine vapor adsorption capacity test results of Q[7]@NH2-MIL-125 adsorbent, Q[7] and NH2-MIL-125 in Comparative Example 1.

[0038] Figure 12 This is a comparison chart of the iodine vapor adsorption capacity of the Q[7]@NH2-MIL-125 adsorbent in Example 1 with the iodine vapor adsorption capacity of materials reported in the prior art.

[0039] Figure 13 The figure shows the results of the iodine adsorption capacity test in the aqueous solutions of Q[7]@NH2-MIL-125 adsorbent, Q[7] and NH2-MIL-125 in Comparative Example 2.

[0040] Figure 14 This is a comparison chart of the amount of iodine adsorbed in the aqueous solution of Q[7]@NH2-MIL-125 adsorbent in Example 1 with the amount of iodine adsorbed in the aqueous solution of materials reported in the prior art.

[0041] Figure 15 The figure shows the adsorption capacity test results of iodine 3 anions in the aqueous solutions of Q[7]@NH2-MIL-125 adsorbent, Q[7] and NH2-MIL-125 in Comparative Example 3.

[0042] Figure 16 This is a comparison chart of the amount of iodine 3 anions adsorbed in the aqueous solution of Q[7]@NH2-MIL-125 adsorbent in Example 1 with the amount of iodine 3 anions adsorbed in the aqueous solution of materials reported in the prior art. Detailed Implementation

[0043] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically specified in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0044] Example 1: Step S1, Synthesis of NH2-MIL-125: NH2-MIL-125 was prepared using a conventional solvothermal method. The standard synthesis procedure is as follows: 0.562 g (3 mmol) of 2-aminoterephthalic acid (NH2-BDC) as the organic ligand was weighed and dissolved in 40 mL of a mixed solvent of N,N-dimethylformamide (DMF) and methanol (volume ratio DMF:methanol = 9:1); then 2.8 mL of glacial acetic acid was added dropwise to control the morphology of the crystal product. Under continuous magnetic stirring for 3 min, 0.592 g (2 mmol) of tetraisopropyl titanate (TPOT) was added dropwise to the above homogeneous solution. The resulting mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel high-pressure reactor and sealed. The reactor was placed in an electric heating oven and heated to 150 °C over 90 min, and then subjected to a static solvothermal reaction for 24 h. After the system cooled naturally to room temperature, the solid product was collected by centrifugation and washed repeatedly with DMF and methanol to remove residual raw materials. The resulting solid powder was finally dried overnight under vacuum at 60°C to obtain pure phase NH2-MIL-125 for later use.

[0045] Step S2, Synthesis of Q[7]@NH2-MIL-125 Adsorbent: Q[7]@NH2-MIL-125 composite material was successfully prepared by a simple loading method. The typical preparation process is as follows: 175 mg (0.1 mmol) of pure NH2-MIL-125 powder obtained in step S1 was uniformly dispersed in 30 mL of methanol to prepare a homogeneous suspension (referred to as solution 1). Another 30 mg (0.025 mmol) of seven-membered cucurbitacin (Q[7]) was completely dissolved in 10 mL of a mixed solvent of water and acetic acid (volume ratio of water:acetic acid = 1:1) to obtain a transparent solution (referred to as solution 2). Then, under continuous vigorous stirring, solution 2 was slowly added dropwise to solution 1. The resulting mixture was stirred continuously at 40 °C for 8 h in the dark. During the reaction, the color of the suspension gradually changed from light yellow to dark yellow. After the reaction was completed, the solid product was collected by centrifugation, and the residue was washed thoroughly with methanol several times to remove the impurities. The product was then dried overnight in a vacuum oven at 60°C to obtain Q[7]@NH2-MIL-125 adsorbent, which was used for subsequent characterization and performance testing.

[0046] The Q[7]@NH2-MIL-125 adsorbent was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). The results are as follows: Figure 1 , Figure 2 , Figure 3 As shown.

[0047] Example 2: Iodine vapor adsorption was performed using the Q[7]@NH2-MIL-125 adsorbent prepared in Example 1. The iodine vapor adsorption experiment was conducted over time as follows: The Q[7]@NH2-MIL-125 adsorbent prepared in Example 1 was dried overnight at 120°C in a vacuum drying oven to remove residual water and organic solvents, thus completing the activation. A 5 mL glass bottle containing 20 mg of pre-weighed activated adsorbent was placed in a 20 mL large glass bottle containing sufficient solid iodine at the bottom, ensuring that the adsorbent and solid iodine did not come into direct contact. The large glass bottle was then sealed tightly and placed in an oven at 75°C under normal pressure. Samples were taken out at different preset adsorption time points. After the samples adsorbed with iodine cooled to room temperature, they were weighed until the sample mass no longer changed. At least three parallel experiments were conducted under each condition to calculate the adsorption capacity.

[0048] The Q[7]@NH2-MIL-125 adsorbent that adsorbed iodine vapor was characterized by X-ray photoelectron spectroscopy (XPS). The characterization data are as follows: Test results as follows Figure 4 As shown, the N1s fine spectrum of X-ray photoelectron spectroscopy (XPS) reveals NI bonds. The results indicate that iodine was successfully adsorbed on the surface of the Q[7]@NH2-MIL-125 adsorbent.

[0049] Example 3: Iodine in aqueous solution was adsorbed using the Q[7]@NH2-MIL-125 adsorbent prepared in Example 1: 5 mg of adsorbent was weighed and immersed in 5 mL of pure iodine solution (300 mg / L, 300 ppm I2). The mixture was stirred continuously at a constant speed of 300 rpm at room temperature. Equal portions of the sample were taken at the preset time point and immediately filtered through a 0.1 μm polyethersulfone (PES) filter membrane. The concentration of residual iodine species in the filtrate was quantitatively determined by ultraviolet-visible spectrophotometry (UV-Vis): the characteristic absorption wavelength of molecular iodine (I2) was set to 453 nm.

[0050] The iodine aqueous solution after adsorption by Q[7]@NH2-MIL-125 adsorbent was analyzed by ultraviolet-visible spectroscopy (UV-Vis), and the characterization data are as follows: Test results as follows Figure 5As shown, the UV-Vis spectrophotometry indicates that the concentration of iodine in the aqueous solution decreases continuously over time. This demonstrates the rapid adsorption of iodine from the aqueous solution by the Q[7]@NH2-MIL-125 adsorbent.

[0051] Example 4: The Q[7]@NH2-MIL-125 adsorbent prepared in Example 1 was used to adsorb iodine 3 ions in aqueous solution: 5 mg of adsorbent was weighed and immersed in 5 mL of iodine-potassium iodide mixed solution (containing 60 mg / L I2 and 120 mg / L KI, total triiodine ions I3). - Concentration 60 ppm). The mixture was continuously stirred at a constant speed of 300 rpm at room temperature. Equal portions were taken at preset time points and immediately filtered through a 0.1 μm polyethersulfone (PES) membrane. The concentration of residual iodine species in the filtrate was quantitatively determined using ultraviolet-visible spectrophotometry (UV-Vis): triiodide ions (I3... - The characteristic absorption wavelength is set to 351 nm.

[0052] The iodine aqueous solution after adsorption by Q[7]@NH2-MIL-125 adsorbent was subjected to UV-Vis detection, and the characterization data are as follows: Test results as follows Figure 6 As shown, the results indicate that the concentration of iodine in the aqueous solution decreases continuously over time. This demonstrates that the Q[7]@NH2-MIL-125 adsorbent effectively absorbs triiodide ions (I3) in aqueous solution. - Rapid adsorption of ).

[0053] Example 5: Q[7]@NH2-MIL-125 adsorbent reuse: The adsorbent was saturated according to Example 3, and the iodine that had been adsorbed into the material was washed off with ethanol. Then it was dried at 60 degrees Celsius to obtain the regenerated Q[7]@NH2-MIL-125 adsorbent. The regenerated Q[7]@NH2-MIL-125 adsorbent was reused in Example 3.

[0054] The results of ultraviolet-visible spectroscopic spectroscopy indicate that, Figure 7 As shown, the Q[7]@NH2-MIL-125 adsorbent can adsorb iodine solution, and the adsorption amount remains basically unchanged even after 5 repeated uses.

[0055] Example 6: Q[7]@NH2-MIL-125 adsorbent reuse: The adsorbent was saturated according to Example 4, and the iodine that had been adsorbed into the material was washed off with ethanol. Then it was dried at 60 degrees Celsius to obtain the regenerated Q[7]@NH2-MIL-125 adsorbent. The regenerated Q[7]@NH2-MIL-125 adsorbent was reused in Example 4.

[0056] The results of ultraviolet-visible spectroscopic spectroscopy indicate that, Figure 8 As shown, Q[7]@NH2-MIL-125 adsorbent can adsorb iodine 3 anion solution, and the adsorption amount remains basically unchanged after being used 5 times.

[0057] Example 7: Monitoring of iodine vapor in the environment by Q[7]@NH2-MIL-125 adsorbent: Iodine vapor was passed through a filter cake loaded with Q[7]@NH2-MIL-125 adsorbent, and the color change of the filter cake over time was observed and recorded. Preparation of filter cake loaded with Q[7]@NH2-MIL-125 adsorbent: A sufficient amount of Q[7]@NH2-MIL-125 powder obtained according to Example 1 was weighed and added to 10 mL of acetonitrile. The mixture was sonicated for 30 minutes to disperse it evenly. Then, a circular filter paper was immersed in the solution until Q[7]@NH2-MIL-125 was evenly loaded on the filter paper. The filter paper was then placed in an oven and dried at 60°C for later use.

[0058] Monitoring results as follows Figure 9 As shown, the results indicate that the Q[7]@NH2-MIL-125 adsorbent undergoes fluorescence quenching within 3 minutes and turns black.

[0059] Example 8: Monitoring of iodine 3 anion aqueous solution in the environment by Q[7]@NH2-MIL-125 adsorbent: Iodine 3 anion aqueous solution was passed through a filter cake loaded with Q[7]@NH2-MIL-125 adsorbent, and the color change of the filter cake over time was observed and recorded. Preparation of filter cake loaded with Q[7]@NH2-MIL-125 adsorbent: A sufficient amount of Q[7]@NH2-MIL-125 powder obtained according to Example 1 was weighed and added to 10 mL of acetonitrile. It was ultrasonically dispersed for 30 minutes. Then, a circular filter paper was immersed in the solution until Q[7]@NH2-MIL-125 was uniformly loaded on the filter paper. The filter paper was then placed in an oven and dried at 60°C for later use.

[0060] Monitoring results as follows Figure 10 As shown, the results indicate that the Q[7]@NH2-MIL-125 adsorbent undergoes fluorescence quenching within 10 seconds, turning reddish-brown in color.

[0061] Comparative Example 1: Referring to Example 2, the only difference was that the Q[7]@NH2-MIL-125 adsorbent was replaced with 2 mg of Q[7] or 18 mg of NH2-MIL-125 obtained according to step S1 of Example 1. The iodine vapor adsorption capacity was tested, and the results are as follows: Figure 11As shown, it can be seen that the adsorption capacity of Q[7]@NH2-MIL-125 adsorbent for iodine vapor is higher than the simple sum of the adsorption capacities of Q[7] and NH2-MIL-125. This indicates that Q[7] and NH2-MIL-125 have a synergistic effect in the Q[7]@NH2-MIL-125 adsorbent system of the present invention, which significantly improves the adsorption capacity of the composite material for iodine vapor.

[0062] Figure 12 The results show the comparison between the iodine vapor adsorption capacity of the Q[7]@NH2-MIL-125 adsorbent in Example 1 of the present invention and the iodine vapor adsorption capacity of materials reported in the prior art.

[0063] Comparative Example 2: Referring to Example 3, the only difference was that the Q[7]@NH2-MIL-125 adsorbent was replaced with 0.5 mg of Q[7] or 4.5 mg of NH2-MIL-125 obtained according to step S1 of Example 1. The iodine adsorption capacity in the aqueous solution was tested, and the results are as follows. Figure 13 As shown, it can be seen that the adsorption capacity of Q[7]@NH2-MIL-125 adsorbent for iodine in aqueous solution is higher than the simple sum of the adsorption capacities of Q[7] and NH2-MIL-125. This indicates that Q[7] and NH2-MIL-125 have a synergistic effect in the Q[7]@NH2-MIL-125 adsorbent system of the present invention, which significantly improves the adsorption capacity of the composite material for iodine in aqueous solution.

[0064] Figure 14 The results show the comparison between the iodine adsorption amount in the aqueous solution of Q[7]@NH2-MIL-125 adsorbent in Example 1 of the present invention and the iodine adsorption amount in the aqueous solution of materials reported in the prior art.

[0065] Comparative Example 3: Referring to Example 4, the only difference was that the Q[7]@NH2-MIL-125 adsorbent was replaced with 0.5 mg of Q[7] or 4.5 mg of NH2-MIL-125 obtained according to step S1 of Example 1. The adsorption capacity of iodine 3 anions in the aqueous solution was tested, and the results are as follows. Figure 15 As shown, it can be seen that the adsorption capacity of Q[7]@NH2-MIL-125 adsorbent for iodine 3 anions in aqueous solution is higher than the simple sum of the adsorption capacities of Q[7] and NH2-MIL-125. This indicates that Q[7] and NH2-MIL-125 have a synergistic effect in the Q[7]@NH2-MIL-125 adsorbent system of the present invention, which significantly improves the adsorption capacity of the composite material for iodine 3 anions in aqueous solution.

[0066] Figure 16The results show the comparison between the adsorption capacity of iodine 3 anions in the aqueous solution of Q[7]@NH2-MIL-125 adsorbent in Example 1 of the present invention and the adsorption capacity of iodine 3 anions in the aqueous solution of materials reported in the prior art.

[0067] Furthermore, it should be understood that after reading the above description of the present invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. A Q[7]@MOF composite material, characterized in that, It includes a seven-membered cucurbit ring assembled together by supramolecular assembly and NH2-MIL-125(Ti).

2. The Q[7]@MOF composite material according to claim 1, characterized in that, The Q[7]@MOF composite material has an octahedral granular morphology; The molar ratio of the seven-membered cucurbit ring to NH2-MIL-125(Ti) is (0.2~0.3):1, preferably (0.24~0.25):

1.

3. The method for preparing Q[7]@MOF composite material according to claim 1 or 2, characterized in that, include: A solution of seven-membered cucurbitacin was obtained by dissolving the seven-membered cucurbitacin in a mixed solvent of water and acetic acid. The seven-membered cucurbit ring solution was added dropwise to the NH2-MIL-125(Ti) dispersion, and stirred at 35~45℃ in the dark. The color of the mixture gradually turned dark yellow. After the reaction was completed, the solid was washed and dried to obtain the Q[7]@MOF composite material.

4. The preparation method according to claim 3, characterized in that, The volume ratio of water to acetic acid in the mixed solvent is (1~2):(1~2).

5. The preparation method according to claim 3, characterized in that, The solvent in the NH2-MIL-125(Ti) dispersion includes methanol.

6. The preparation method according to claim 3, characterized in that, The stirring reaction takes 8 to 12 hours.

7. The application of the Q[7]@MOF composite material according to claim 1 or 2 as or for making an adsorbent.

8. The application of the Q[7]@MOF composite material according to claim 1 or 2 for the adsorption of iodine.

9. The application according to claim 8, characterized in that, The iodine includes iodine vapor, iodine molecules in iodine solution, and I3. - One or more of them.

10. The application according to claim 8 or 9, characterized in that, The Q[7]@MOF composite material is used to adsorb iodine at a temperature of room temperature to 130℃.